The Resilience Power and Existence of Pesantren Lirboyo and Al-Falah Kediri During the Post-Covid 19 Pandemic - Fanani, Moh. Zainal (Didaktika Religia, 2022)
This study aims to determine the strategy of Pesantren Lirboyo and Al-Falah Ploso in Kediri in maintaining their resilience power and existence after the COVID-19 pandemic to become more resilient pesantren. This study uses a qualitative approach, with the research subjects Pesantren Lirboyo and Al-Falah Ploso Kediri. The method of data collection is through observation, interviews, and documentation. The data obtained were then analyzed in stages: data display, reduction, and verification. The results found: 1) The preparations conducted by Pesantren Lirboyo and Ploso Kediri to create more resilient pesantren are: Maintaining cleanliness of the cottage and enforcing health protocols; Implementing indicators of resilient pesantren; Support from the government; Preparing students who will return to the pesantren and cooperation with the covid task force. 2) The efforts of Pesantren Lirboyo and Ploso in Kediri to create more resilient pesantren, namely: Realizing healthy pesantren; Preparing human resources; Preparing sufficient budgets; Increasing students' understanding of indicators of resilient pesantren; Increasing students' awareness of adopting lifestyle; Maintaining the cleanliness of the cottage environment; Preparing health facilities; Full support from the guardians of students, and Instilling the value of belief in students that the COVID-19 outbreak is a test from Allah. 3) The obstacles for Pesantren Lirboyo and Ploso in Kediri to create a resilient Pesantren are: Difficulty in implementing health protocols (physical distancing); teachers and students are not familiar with the use of information technology to support online learning; The process of returning students to pesantren through the stages is quite long and through a strict health screening; and Pesantrens do not yet have special facilities for student quarantine.